Desain Sistem Monitoring Pengolahan Sampah Organik Maggot Berbasis Internet Of Things - Muhammad, Youri; Sumaryo , Sony; Permana , Agus Ganda (eProceedings of Engineering, 2024)
Waste is the most common problem found today. It is still often seen that waste is not in its place or officers have not disposed of waste in the garbage disposal, things like this can cause discomfort during activities and even cause air pollution. One way to process organic waste is by decomposing organic waste with maggots. Therefore, officers must monitor the processing of organic waste. Generally, the processing of organic maggot waste is monitored through temperature, pH and weight to determine the condition of the maggots when processing organic waste. To make it easier to monitor the processing of organic maggot waste which is currently still done manually and will take a long time, this study aims to design and implement a tool that can monitor the processing of organic maggot waste using a temperature sensor module, pH sensor and weight sensor which is then connected to the NodeMCU ESP8266 which functions as a microcontroller that will process and then send the data to be displayed to users via the application. This study succeeded in monitoring the processing of organic maggot waste based on temperature, pH and weight with a temperature sensor error rate of 1.32%, a pH sensor of 1.2%, and a weight sensor of 2.9%. The results of this monitoring can be a reference for officers to process organic maggot waste to keep it in good condition. Keywords— organic waste, maggot, monitoring system, IoT